Effects of printing parameters on the mechanical strength of thermoplastics 3D printed specimens / Mohammad Azeeb Mazlan ... [et al.] - Mazlan, Mohammad Azeeb; Mustar, Muhammad Fadil; Abdullah, Abdul Halim; Che Zakaria, Noor Ayuni; Mohamad Hashim, Natiara; Pangesty, Azizah Intan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
3D printing is increasingly adopted in the biomedical field, particularly for developing adaptive assistive devices. Common materials for Fused Deposition Modelling (FDM) include Polylactic Acid (PLA), Acrylonitrile Butadiene Styrene (ABS), and Polyethylene Terephthalate Glycol (PETG). With the growing demand to identify the best materials and parameter settings for these applications, our project focuses on creating a 3D model of tensile test specimens with varying infill densities, wall perimeters, and layer heights for both ABS and PETG materials. Our goal is to evaluate how these parameter settings affect the tensile properties of each material. We fabricated the 3D specimen model following ASTM D638-14 Type I dimensions and conducted tensile tests using a Universal Testing Machine at a 5mm/min feed rate. Our results indicate that increasing infill density enhances Young's modulus and tensile strength for both ABS and PETG materials. Young's modulus for ABS shows marginal improvement with different wall perimeters. A similar trend is observed in Young's modulus and tensile strength for ABS and PETG at different layer heights. PETG exhibits higher tensile strength, while ABS demonstrates greater stiffness